Community of Practice Through Learning from Others (LEAF) Activities to Improve Auditor Competence at the Supreme Audit Agency (BPK) - Elliya Nurul Firdaus; Irfan Setiawan; Marthalina, Marthalina (Sean Institute, 2026)
As the complexity of audits has increased, the Audit Board of Indonesia (BPK) has initiated the development of auditors’ competencies through LEAF, which applies an integrated learning strategy. However, LEAF faces four challenges: inadequate learning needs analysis, the unclear measurement of its contribution to improving auditors’ competencies, the underutilization of knowledge assets within BPK, and the lack of assurance regarding post-LEAF sustainability. This study aims to analyze the design and implementation of LEAF at BPK, the contribution of LEAF to the development of BPK auditors’ competencies, and the efforts undertaken by BPK to ensure the sustainability of LEAF. The analysis is based on Etienne Wenger’s (1998) community of practice theory, which encompasses the dimensions of domain, community, and practice, as well as Sedarmayanti’s (2016) civil servant competency development theory, which includes the dimensions of technical skills and human relations skills. This study employs a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that LEAF constitutes a modified community of practice that utilizes the three corporate university learning strategies: formal, social, and experiential learning. The design of LEAF meets the requirements of a community of practice by fulfilling the dimensions of domain, community, and practice. Nevertheless, several weaknesses remain in the implementation of LEAF as a community of practice. These include the reliance of LEAF’s needs analysis on the portfolios of subject matter experts, the lack of sustained interaction among LEAF members within the community dimension, and the limited utilization of knowledge assets across BPK within the practice dimension. LEAF also has a positive impact on improving auditors’ competencies at BPK, both in terms of technical skills and human relations skills, although continuous development of the instruments used to assess LEAF’s contribution to competency development is still required.